Endoscopic butterfly cartilage myringoplasty. (1st February 2016) - Özgür, Abdulkadir; Dursun, Engin; Terzi, Suat; Erdivanlı, Özlem Çelebi; Coşkun, Zerrin Özergin; Oğurlu, Mahmut; Demirci, Münir
Abstract: Conclusion : Based on the results of this study, it is believed that, in appropriate patients with tympanic membrane perforation, the endoscopic butterfly cartilage myringoplasty can be applied, with a shorter operation time, high graft success rate, and low risk of complications. Objective : The aim of this study was to evaluate the results of the endoscopic butterfly cartilage myringoplasty in terms of the graft success rate and hearing gain. Methods : Forty-five ears of the 42 patients who were subjected to endoscopic butterfly cartilage myringoplasty surgery between January 2013 and December 2014 were included in this study. The archival records of the patients were reviewed retrospectively, evaluating the pre-operative and post-operative hearing results and post-operative graft success rates in the early and late periods. Results : The graft success rates were 97.8% (44/45 ears) and 95.6% (43/45 ears) at the post-operative 1- and 6-month follow-ups, respectively. When the post-operative air conduction hearing thresholds were compared, significant improvement was seen at post-operative 1- and 6-month follow-ups in the hearing thresholds, when compared to the pre-operative levels ( p  < 0.001).